Ethnolinguistic character of applied geometry terms of «measure», «dimension» - Kemelbekova, Э.А.; Syzdykova, Г.О. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
This article is devoted to one of the topical issues in the field of applied geometry, the explanation of terms reflecting our national identity and spirituality, the definition of the way to create them. The study considers the ethnolinguistic, semantic nature of the units of measurement of length, distance, volume, space in terms of applied geometry. In order to form a national vision and understanding of the terms of applied geometry, the main task of this research work is to analyze the etymology, ethnolinguistic meaning and scope of the above-mentioned concepts of measure in the process of language development. In this regard, the interpretation and explanations of the names, expressing the concepts of measures in terms of cognition of the Kazakh people are given . The purpose of the research is a comparative analysis of the ethnolinguistic nature of names expressing the concept of measures of applied geometry (length, distance, volume, space, thickness, depth, height, etc.) in Kazakh, Russian and English. Linguistic, ethnographic, scientific works of foreign and Kazakhstani scientists served as the material for the analysis, as well as etymological, explanatory dictionaries were used in the work. Etymological aspects of the terms taken as the object of research are analyzed within the framework of ethnology, cultural studies, cognitive units. The authors come to the conclusion that the concepts of “measures” and “measurements” are a channel connecting consciousness with national existence. The representation of the world in the context of the concept of “measures” defines the role of linguistic units as a cultural code in the spiritual space.